Corporate Criminal Liability Arrangements in the IUS Constituendum - Mohammad Fajarudin (Green Publisher Indonesia, 2021)
The development of science and technology and globalization were already unstoppable today, not only have a beneficial impact, but also often have a negative impact for example by the